Development and investigation of Pongamia pinnata epoxy composites. (2020) - Navaneethakrishnan, G.; Karthikeyan, T.; Saravanan, S.; Selvam, V.; Parkunam, N.
Abstract: In the modern developments to increase the concerns in the natural fibers and its applications in different fields. In this paper, the development and investigation of Pongamia pinnata epoxy composites by compression moulding method. The 20 wt% composites have more mechanical strength as compared to other composites because of the uniform distribution of load. The scanning electron microscopy (SEM) shows the morphology of composites and ensures the presence of fiber reinforcement.